A Community of monastic development practice: the formation of a nationwide collaborative development monk network. Issue 5 (4th July 2022) - Southard, Dylan
ABSTRACT: The importance of development strategies that emphasise local agency and authenticity has long been recognised, but these goals often preclude the access to the extralocal resources and knowledge systems available to large-scale top-down organisations. This paper presents the case of development monks in Thailand, who have recently begun selectively adopting the practices of their state and civil society collaborators. Modelled after the organisational structures of development NGOs, government agencies, and the Thai Sangha, development monk networks facilitate a community of monastic development of practice, through which practitioners' skills are honed, resources are procured, and knowledge and meanings are shared and negotiated.